Thirteen Days to Midnight - Carman, Patrick (London Little, Brown and Company, 2011)
In the aftermath of the accident that killed his foster father, Jacob Fielding discovers that he has acquired the power of indestructibility, and as he learns about it he comes to realize that it is a heavy burden, if not a curse.
Keywords: Paranormal fiction -- Orphans -- Death